Expanding the limits towards 'one-pot' DNA assembly and transformation on a rapid-prototype microfluidic device. Issue 19 (9th August 2021) - Perry, James M.; Soffer, Guy; Jain, Raja; Shih, Steve C. C.
Abstract : A rapid-prototype digital microfluidic platform for assembly and transformation of large plasmids – aided by a novel electrode design, a closed-loop water replenishment system, and a precisely tuned temperature control system. Abstract : DNA assembly and transformation are crucial to the building process in synthetic biology. These steps are significant roadblocks when engineering increasingly complex biological systems. To address this, recent development of widespread 'biofoundry' facilities has employed automation equipment to expedite the synthetic biology workflow. Despite significant progress, there is a clear demand for lower-cost and smaller-footprint automation equipment. The field of microfluidics have emerged to provide automation capabilities to meet this demand. However, we still lack devices capable of building large multi-gene systems in a consolidated process. In response to this challenge, we have developed a digital microfluidic platform that performs "one-pot" Golden Gate DNA assembly of large plasmids and transformation of E coli . The system features a novel electrode geometry and modular design, which make these devices simple to fabricate and use, thus improving the accessibility of microfluidics. This device incorporates an impedance-based adaptive closed loop water replenishment system to compensate for droplet evaporation and maintain constant assembly reaction concentrations, which we found to be crucial to the DNA assembly efficiency. We also showcase a closed-loop temperature control system that generates precise thermodynamic profiles to optimize heat shock transformation. Moreover, we validated the system by assembling and transforming large and complex plasmids conferring a biosynthetic pathway, resulting in performance comparable to those of standard techniques. We propose that the methods described here will contribute to a new generation of accessible automation platforms aimed at speeding up the 'building' process, lowering reagent consumption and removing manual work from synthetic biology.